A "Complex" Issue: Deciphering the Role of Variant PRC1 in ESCs. - Bracken, Adrian (My University, 2013)
Several noncanonical type-1 Polycomb Repressive Complexes (PRC1) that act independently of PRC2 have been recently identified, but their functions in embryonic stem cells (ESCs) are unclear. Two recent reports by Morey et al. (2012a) and Wu et al. (2013) define functionally distinct roles for canonical and noncanonical PRC1 in ESCs.
PUBLISHED
Keywords: type-1 Polycomb Repressive Complexes (PRC1); type-1 Polycomb Repressive Complexes (PRC1); Cancer; Genes & Society